2014
DOI: 10.1155/2014/437307
|View full text |Cite
|
Sign up to set email alerts
|

An ICT-Based Diabetes Management System Tested for Health Care Delivery in the African Context

Abstract: The demand for new healthcare services is growing rapidly. Improving accessibility of the African population to diabetes care seems to be a big challenge in most countries where the number of care centers and medical staff is reduced. Information and communication technologies (ICT) have great potential to address some of these challenges faced by several countries in providing accessible, cost-effective, and high-quality health care services. This paper presents the Mobil Diab system which is a telemedical ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 11 publications
(10 reference statements)
0
61
0
Order By: Relevance
“…These results exhibited consistent findings with no heterogeneity. One study reported a reduction larger than clinically anticipated, which raised debate over the legitimacy of their findings (26). After excluding the subgroup of studies that were assessed as poor quality, we found a mean reduction of 0.41% (95% CI 0.22, 0.61; P , 0.001; I 2 = 0%) (Fig.…”
Section: Type 2 Diabetesmentioning
confidence: 83%
See 2 more Smart Citations
“…These results exhibited consistent findings with no heterogeneity. One study reported a reduction larger than clinically anticipated, which raised debate over the legitimacy of their findings (26). After excluding the subgroup of studies that were assessed as poor quality, we found a mean reduction of 0.41% (95% CI 0.22, 0.61; P , 0.001; I 2 = 0%) (Fig.…”
Section: Type 2 Diabetesmentioning
confidence: 83%
“…In the type 2 diabetes studies, the mean age of the participants was much higher, ranging from 51 (17) to 62 years old (18), and the mean duration of diabetes ranged from 5 (19) to 13 years (20) from six studies. Four studies were undertaken in Europe (18,(20)(21)(22), three in the U.S. (17,23,24), two in Asia (19,25), and one in Africa (26).…”
Section: Characteristics Of the Included Studies And Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The single study from Africa8 included only 40 people with type 2 diabetes and showed an unexpectedly large 1.7% reduction in HbA1c in the intervention group. However, because of several flawed methodological aspects, this African study was considered to be of poor quality, providing unreliable data, in the meta-analysis 6…”
Section: Introductionmentioning
confidence: 99%
“…It enables diabetes patients to manage their own lifestyle data around the clock using their mobile devices (Android, iPhone, and iPads) and/or web-based applications. The platform also enables medical care personnel to access patients' data through a protected web portal (Takenga et al 2014). Another multidisciplinary project was proposed to promote and motivate healthy lifestyles using assistive technology.…”
Section: Motivation In Diabetic Patientmentioning
confidence: 99%